Mental health disorders among Rohigya refugees in Malaysia / Kushilpal Kaur Satwant Singh - Kushilpal Kaur, Satwant Singh (2021)
Mental health disorders among refugees has been recognized as a major public health issue. However, to date, there is limited evidence on the prevalence of Mental health disorders among Rohingya refugees residing in transit countries such as Malaysia. This study aimed to examine the prevalence and associated factors of Major Depressive Disorder (MDD), generalized anxiety disorder (GAD) and post-traumatic stress disorder (PTSD) among Rohingya refugees in Malaysia. Adult Rohingya refugees residing in Selangor (n= 220) were randomly selected to participate in this cross-sectional study that was conducted from June to November 2019. Perceived social support, religious orientation, and food security was assessed using the Multidimensional Scale of Perceived Social Support (MSPSS), Religious Orientation Scale-Revised (ROS-R) and the Radimer/Cornell food insecurity instrument. Mini-International Neuropsychiatric Interview (MINI) was used to examine MDD, GAD, and PTSD. The prevalence of GAD, PTSD, and MDD was reported at 92 (41.8%), 84 (38.2%) and 71 (32.3%). Several factors were significantly associated with MDD following multivariate analysis namely being female (AOR = 2.54; 95% CI 1.21, 5.34), living in Malaysia for less than 1 year (AOR = 6.95; 95% CI 1.89, 25.57), having been physically injured (AOR = 3.25; 95% CI 1.52, 6.96), perceived low/moderate social support (AOR = 2.17; 95% CI 1.13, 4.19) and food insecurity (AOR = 2.77; 95% CI 1.19, 6.47). Exposure to violence (AOR = 38.46; 95% CI 16.27, 90.91) and food insecurity (AOR = 3.74; 95% CI 1.41, 9.91) were significantly associated with PTSD. The findings of this study provide new evidence relating to the burden and risk factors of Mental health disorders among Rohingya refugees residing in Malaysia, addressing these risk factors could improve mental health among this population.